The benefits and limitations of using blue-blocking filters – a review of results of clinical trials - Partyka, Aleksandra; Dyrek, Martyna; Sikorski, Piotr; Sikorska, Ewa (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Blue light is part of the natural light spectrum and plays a role in regulating the circadian rhythm. However, with the increasing use of electronic devices and energy-efficient lighting emitting high levels of artificial blue light, concerns are raised regarding its potential effect on human health. Blue-blocking filters have been developed and are adver tised as a solution to be used in spectacles or intraocular lenses. This review aims to provide an in-depth analysis of the use of blue-blocking filters based on the results of clinical trials. Material and methods. This review included relevant original papers reporting on clinical trial results from PubMed, Science Direct, and Google Scholar databases using specified keywords. Analysis of the literature. Trials conducted with patients reveal mixed results, with some showing no significant changes in vision and reading abilities, while others indicating potential limitations such as reduced contrast vision. However, blue-blocking filters have demonstrated potential benefits in improving sleep quality and mood, particularly in patients with sleep disturbances or psychiatric disorders. The efficacy of blue-blocking filters in mitigating symptoms of digital eye strain remains inconclusive. Conclusion. Overall, this paper provides a comprehensive assessment of the benefits and limitations associated with the use of blue-blocking filters, highlighting the need for further investigation in certain areas.
Keywords: blue light; blue-blocking filters; clinical trials